Analysis of Healthcare Services Based on Local Wisdom and Holistic Care in Relation to Patient Loyalty: JEL Classification: I10, I12, I18, L84, M31 - Cahyaningrum, Rina Asih Budi; Isa, Muzakar; Soekiswati, Siti (Journal La Bisecoman, 2025)
Health services that focus solely on medical aspects often fail to address patients’ comprehensive needs. Integrating local wisdom and holistic care offers a strategic approach to enhance service quality. Local wisdom reflects community cultural values, while holistic care addresses physical, psychological, social, and spiritual dimensions. Together, they can strengthen hospital image, increase satisfaction, and build loyalty. PKU Muhammadiyah Karanganyar Hospital, grounded in religious and cultural values, is well-positioned to apply this model. This study analyzes the influence of services based on local wisdom and holistic care on patient loyalty, with hospital image and satisfaction as mediators. A quantitative cross-sectional design was used, involving 205 patients surveyed with closed-ended questionnaires. Data were analyzed using SEM-PLS with SmartPLS software. Findings show that services rooted in local wisdom positively influence hospital image, though modestly. Holistic care has a stronger impact on both image and satisfaction. Mediation analysis indicates that hospital image and satisfaction significantly link service provision to loyalty. Hospital image has a moderate effect on loyalty, while satisfaction plays a more direct role. The results suggest that cultivating a strong image and delivering comprehensive care are essential to fostering loyalty. Holistic care emerges as the dominant factor shaping positive perceptions and satisfaction. The study concludes that integrating cultural values with holistic care effectively strengthens patient relationships. Such a strategy should be a cornerstone of hospital service improvement.